Pengaruh Penggunaan Uang Elektronik Terhadap Perilaku Konsumtif Mahasiswa (Survey Terhadap Mahasiswa Pendidikan Ekonomi Universitas Siliwangi Angkatan 2020-2023) - Maherina, Rina; Sadiah, Ati; Srigustini, Astri (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to find out how the use of electronic money affects students' consumptive behavior. The main problem in this research is the existence of consumer behavior that occurs in Economics Education students at Siliwangi University. This research uses a quantitative approach with survey research methods with data collection techniques using questionnaires. The population in this study was all economic education students from the 2020-2023 class of Siliwangi Tasikmalaya University, namely 490 students. Sampling in this research used purposive sampling technique. The sample used was based on the Slovin formula calculation, namely 220 respondents from Economic Education students who used electronic money. The data processing technique uses the help of IBM SPSS Statistics 20 with data analysis techniques, namely the t test (partial) with a significance level of 5% or 0.05. Based on the research results, it is known that there is a significant influence of 6% of the use of electronic money on the consumptive behavior of Economic Education students class 2020-2023 at Siliwangi Tasikmalaya University.